Critiquing “Neoliberalism”: Three Interrogations and a Defense - Phelan, Sean (Peter Lang Publishing Inc., 2014)
Looked at broadly, we can identify two distinct discourses about neoliberalism in communication and media studies and elsewhere. The first deploys the term to enact a familiar critical narrative, where neoliberalism signifies a social order dominated by the logic of the market. This narrative has been given different inflections in communication and media research. Neoliberalism has functioned as a descriptive and explanatory category in analyses of topics such as infotainment (Thussu, 2007), media ownership (Herman & McChesney, 1997), multiculturalism (Lentin & Titley, 2011), reality television (Ouellette & Hay, 2008), political marketing (Savigny, 2008), intellectual property rights (Hesmondhalgh, 2008), and the cultural politics of voice (Couldry, 2010). Others have examined the communicative dynamics of “free market” regimes without explicitly deploying the term “neoliberalism” (Aune, 2001). More generally, the role of media and communication practices in the ideological constitution of neoliberalism is taken for granted in the wider literature (see Birch & Mykhnenko, 2010; Harvey, 2005). [First paragraph.]
Keywords: Neoliberalism; Communication and media studies